Large Classes and English Language Teaching and Learning in Public Sector Secondary Schools of Pakistan - Shagufta Moghal; Asma Shahid Kazi; Ammaira Bukhari (Institut Agama Islam Negeri Palopo, 2019)
This study aimed to explore the Pakistani secondary teachers' perceptions towards teaching English in large classes and to find out how they coped with the challenges which come with teaching such classes. The data was collected through semi structured interviews, with eight secondary school teachers currently working in the public sector schools of Lahore, Pakistan. The data was analyzed inductively through repeated engagement with the interview transcripts. Research results indicated that teaching large classes had many issues and problems, such as lack of space, facilities and resources; inability to pay attention to every student; high noise levels; time constraints; problems with assessment of a large number of students; and limited opportunities of interaction between teacher-student and student-student. The discussion highlighted the teaching and learning strategies employed by teachers in their classrooms in the Pakistani context, which include the use of pair and group work, notional time, peer correction and self-editing to improve assessment.